PENGATURAN HUKUM SERTIFIKAT HAK ATAS MEREK SEBAGAI JAMINAN FIDUSIA DALAM PROSES PENGAJUAN KREDIT DI PERBANKAN BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 - Made Bagus Satria Yudistira (University of Udayana, 2017)
United Nations Commission on Intellectual Trade Law (UNCITRAL) in a conference held on 39th round in 2006, this round brought to the result of intellectual properties, specifically on the Trademarks that has been the source of bank financing. Then the things that to be discussed regarding to the legal arrangements of the rights certificate on the trademark as fiduciary assurance in the process of application for bank credit and also the ideal form provisions of the trademark as an object that used as an assurance object. The purpose of this writing is to find the explication of the rule of law concerning about the rights provision to the trademark as a fiduciary assurance after the issuance of the constitutions number 20 of 2016 about trademark and geographical indications, because in that constitution there was nothing firm as it stated on the article that related to the rights of the trademark as fiduciary assurance or the norm is blurred and implicitly stated that the rights of the trademark can be used as an object of fiduciary assurance. Besides that there was also the non-law factor and the bank policy that complicates the process in banking. Nevertheless there is a legal basis that arranged by the constitutions number 42 of 1999 regarding the fiduciary assurance and the code of civil law concerning the elements of the trademark that can be used as fiduciary assurance in the process of credit application. United Nations Comission on Intellectual Trade Law (UNCITRAL) dalam pertemuan yang diselenggarakan pada putaran ke 39 yaitu pada tahun 2006, putaran in menghasilkan kekayaan intelektual, khususnya Merek telah menjadi sumber pembiayaan Perbankan. Maka yang perlu dibahas mengenai Pengaturan Hukum sertifikat Hak atas Merek sebagai jaminan Fidusia dalam proses pengajuan kredit di perbankan serta ketentuan wujud ideal dari merek sebagai benda yang dijadikan obyek jaminan. Tujuan dari Penulisan adalah mencari kejelasan aturan hukum mengenai ketentuan Hak atas merek sebagai jaminan fidusia setelah diterbitkannya Undang-undang no 20 tahun 2016 tentang Merek dan Indikasi Geografis, karena di dalam Undang-undang tersebut tidak menyatakan dengan tegas Pasal yang berkaitan dengan hak Merek sebagai jaminan fidusia atau norma kabur yang tidak secara tegas menyatakan Hak atas Merek dapat dijadikan objek sebagai Jaminan fidusia. Di samping itu juga terdapat faktor non-hukum serta kebijakan Bank yang mempersulit prosesnya di perbankan. Walaupun demikian sesungguhnya terdapat dasar hukum yang diatur oleh Undang-undang no 42 tahun 1999 tentang jaminan Fidusia dan Kitab Undang-undang hukum Perdata mengenai unsur-unsur Merek bahwa dapat dijadikan sebagai jaminan fidusia dalam proses pengajuan kredit.